2020
DOI: 10.1016/j.neuropharm.2020.108240
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of mGlu5 receptors with the positive allosteric modulator VU0360172, modulates thalamic GABAergic transmission

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…These effects are hypothesised to represent changes in protein expression or location. A recent study [ 90 ] showed that incubation of thalamic slices in VU030172 (5 μM) for 1 h could change the tonic GABA-A receptor current, an effect that appeared to result from a change in GABA uptake and GAT-1 expression. These effects occurred without changes in GAT-1 mRNA and thus do not represent increased transcription but could result from GAT-1 trafficking or increased translation.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are hypothesised to represent changes in protein expression or location. A recent study [ 90 ] showed that incubation of thalamic slices in VU030172 (5 μM) for 1 h could change the tonic GABA-A receptor current, an effect that appeared to result from a change in GABA uptake and GAT-1 expression. These effects occurred without changes in GAT-1 mRNA and thus do not represent increased transcription but could result from GAT-1 trafficking or increased translation.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in the expression and function of mGlu5 receptors have been found in the thalamus and somatosensory cortex of WAG/Rij rats, and pharmacological enhancement of mGlu5 receptors with a selective positive allosteric modulator (PAM) was found to reduce SWD frequency in these rats without the development of tolerance (Ngomba et al, 2011;D'Amore et al, 2013;Celli et al, 2020). Present findings suggest that, in WAG/Rij rats, mGlu5 receptors are dysfunctional also in the hippocampus, and this may underlie some cognitive abnormalities observed in these animals (van Luijtelaar et al, 1989;Karson et al, 2012;Jafarian et al 2015;Malyshev et al, 2012;Leo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Expression and function of mGlu1 and mGlu5 receptors are reduced in the thalamus of symptomatic WAG/Rij rats, and systemic administration of selective mGlu1 or mGlu5 positive allosteric modulators reduces SWD incidence in these animals (Ngomba et al, 2011;D'Amore et al, 2013;. In particular, pharmacological activation of mGlu5 receptors up-regulates the high affinity GABA transporter, GAT-1, and restrains tonic inhibition in the VBT of WAG/Rij rats (Celli et al, 2020), a mechanism that may protect against absence seizures by reducing hyperpolarization in VBT neurons.…”
mentioning
confidence: 99%
“…855/2020-PR]. Immunoblots were analysed as described before [ 35 , 36 ]. OX1 receptors were detected by using rabbit polyclonal antibody (anti-OX1, AB3092, Chemicon, Millipore Corporation, Billerica, MA, 1:1000) and mouse monoclonal antibody for β-actin (1:50000, Sigma, St. Louis, MO).…”
Section: Reduced Ox1 Receptor Expression In the Thalamus And Somatose...mentioning
confidence: 99%